Factors Influencing Repurchase Intention of Scarlett Whitening: Product Quality, Variety, and Celebrity Endorsement - Pratita, Mutya Paramita; Enzella Chrisdianthi; Guruh Ghifar Zalzalah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to determine the influence of product quality, product variation, and celebrity endorsement on repurchase intention of Scarlett Whitening. The sample in this study consisted of 100 respondents. The technique used in this research employed non-probability sampling technique with purposive sampling method. Data analysis in this study utilized SPSS for Windows 24.0 with multiple linear regression analysis technique at a significance level of α = 0.05. The results of the study indicate that partially, product quality, product variation, and celebrity endorsement have a significant effect on repurchase intention. The magnitude of the influence of product quality, product variation, and celebrity endorsement is indicated by the Adjusted R Square value of 57.6%. Suggestions for further research include exploring other factors that may influence repurchase intention besides product quality, product variation, and celebrity endorsement.